Narrative Crossroads in Ecuadorian Fieldwork - Verdad, Universidad; Abad, Matías; Ullauri, Narcisa; Carr, Anne (Universidad-Verdad, 2020)
The qualitative researcher is often described as a bricoleur who prepares a representation from multiple fragments of documentation yet, always involved in one way or another paying attention to situatedness and its neglected possibilities and temporalities in the web of everyday research life. At this narrative crossroads, fieldwork practices constitute ethnographic concepts composed of both separation and connection and are thus worlding tools that enable political thought and practice beyond the onto-epistemic limits of modern knowledge. In revisiting our fieldwork narratives from the paramo of the Southern Andes and the beach of the Pacific Coast of Ecuador, we begin to explore the neglected epistemic potential from the hands-on agencies of the practical and material consequences of our thinking. ***** El investigador cualitativo se describe a menudo como un bricoleur que prepara una representación a partir de múltiples fragmentos de documentación, pero siempre, de una forma u otra, prestando atención a la situacionalidad y sus posibilidades y temporalidades desatendidas en la red de la vida cotidiana de la investigación. En esta encrucijada narrativa, las prácticas de trabajo de campo constituyen conceptos etnográficos compuestos tanto de separación como de conexión y, por lo tanto, son herramientas de mundo que permiten el pensamiento y la práctica políticos más allá de los límites onto-epistémicos del conocimiento moderno. Al revisar nuestras narrativas de trabajo de campo del páramo de los Andes del Sur y la playa de la Costa Pacífica de Ecuador, comenzamos a explorar el potencial epistémico desatendido de las agencias prácticas de las consecuencias reales y materiales de nuestro pensamiento.